Social Capital Household Welfare and Poverty: Evidence from Pakistan (The Pakistan Development Review, 2016)
The research addresses the missing link between social capital and analyses of household welfare and poverty. First the relationship between social capital and household welfare is analysed using a social capital index and a heterogeneity index. The social capital index is calculated using different dimensions: density of membership, attendance at meetings, cash and kind contributions and decision making in local organisations/associations. Heterogeneity index is based on differences in incomes, ethnicity, education and political affiliations in the composition of organisations. Endogeneity of social capital with household expenditure is tested through an Instrumental Variable approach. The relationship between social capital and probability of being poor is analysed through a logit model. The analysis uses data collected form 1050 households in and around the cities of Karachi, Lahore and Quetta. The main results indicate that social capital (however measured) has a positive impact on the welfare of the household. The study concludes that social capital and human capital have the same returns. A powerful result of the research is that households with social capital at their disposal are likely to be less poor and that poverty is less when households share risks though building associations and through collective action. The research has some policy implications which can be useful in building up social capital in the country.